Decreased and Heterogeneous Neutralizing Antibody Responses Against RBD of SARS-CoV-2 Variants After mRNA Vaccination - Hernández-Luis, Pablo; Aguilar, Ruth; Pelegrin-Pérez, Judit; Ruiz-Olalla, Gemma; García-Basteiro, Alberto L.; Tortajada, Marta; Moncunill, Gemma; Dobaño, Carlota; Angulo, Ana; Engel, Pablo (Frontiers in Immunology, 2022)
The rapid spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) emerging variants raises concerns about their capacity to evade immune protection provided by natural infection or vaccination. The receptor-binding domain (RBD) of the viral spike protein is the major target of neutralizing antibodies, and viral variants accumulate mutations in this region. In this study, we determined the antibody neutralization capacity against the RBD of SARS-CoV-2 variants Alpha (B.1.1.7), Gamma (P.1), Epsilon (B.1.427), Kappa (B.1.617.1), and Delta (B.1.617.2) in a cohort of healthcare workers naturally infected or receiving COVID-19 mRNA vaccines from Moderna or Pfizer-BioNTech. We show that the five RBD variants displayed an augmented binding to ACE2 compared to the original Wuhan strain. The most significant increase was observed in variants Epsilon and Delta, containing mutation L452R. Using a flow cytometry cell-based assay, we found that SARS-CoV-2-infected subjects presented low levels of RBD-specific neutralizing antibodies against all variants analyzed, except Alpha. However, the neutralizing activity incremented considerably after a subsequent mRNA-vaccine dose, to levels significantly higher than those in naïve individuals receiving two vaccine doses. Importantly, we observed partially impaired neutralizing responses against most variants in fully vaccinated individuals. Variants Gamma and Kappa encompassing RBD E484K/Q mutations presented the highest neutralizing resistance. Furthermore, a wide heterogeneity in the magnitude of RBD-specific neutralizing responses against all tested SARS-CoV-2 variants following both mRNA vaccines was detected. Altogether, our findings provide important knowledge regarding SARS-CoV-2 vaccine-induced immunity, and should be very useful to guide future vaccination regimens and personalized vaccine approaches.